Tracking key metrics: fluctuations in external and internal load across game quarters in collegiate basketball players - Zhang, S.; Li, M.; Qin, S.; Xing, W.; Zhai, Z.; Wang, X. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aimed to explore the quarter-by-quarter variations in external and internal load and their interrelationships throughout basketball games among collegiate basketball players.